Assisting Communication Partners in the Setting of Treatment Goals: The Development of the Goal Sharing for Partners Strategy - Preminger, Jill E.; Lind, Christopher (Seminars in Hearing, 2012)
The Goal Sharing for Partners Strategy (GPS) is a tool for audiologists to use with patients with hearing loss (PHLs) and their communication partners (CPs). This strategy provides a framework that is designed to assist both the PHL and their CP to (1) acknowledge the hearing loss; (2) acknowledge the hearing loss-related activity limitations and participation restrictions that they each face as a result of the hearing loss; (3) acknowledge that they are partners in communication; and (4) develop an understanding of their shared responsibility in dealing with the hearing loss. The GPS is a shared goal-setting strategy that enables PHLs and their CPs to develop realistic mutually derived communication goals and to consider the steps necessary to achieve these goals. The purpose of this article is to outline the need for the GPS, to present the theoretical background for its development, and to describe the steps necessary to use this new tool. Both a step-by-step GPS road map is described, as well as suggestions for using the GPS as a framework for including CPs in the audiological rehabilitation process.
Keywords: Audiological rehabilitation; hearing loss; communication partners